2021
DOI: 10.1371/journal.pone.0260298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of CYP2R1 (rs10741657) in Bangladeshi adults with low serum 25(OH)D level—A pilot study

Abstract: Background Some studies revealed that despite having sufficient sun exposure and dietary supply, the level of serum 25(OH)D in Bangladeshi adults is lower than its normal range. Genetic pattern of an individual is also an essential factor that regulates the level of serum 25(OH)D. However, the genetic variations of CYP2R1 (rs10741657) and their association with low serum 25(OH)D level in Bangladeshi adults are yet to be explored. Objective This study was conducted to determine the frequency of variants of rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…In this research, the most common frequency distribution for the heterozygous genotype was the GA genotype, with 33 people (39.3%), and the least common genotype was the AA genotype with 20 people (23.8%). This result is in accordance with a study on healthy individuals in Denmark, and a study on unhealthy individuals in Jordan, Serbia, and Chennai (India), where the GA genotype of CYP2R1 rs10741657 was the largest genotype amount that was reported, but it was not in accordance with a study with healthy subjects in Singapore, Jordan, and Bangladesh, that reported the GG genotype in CYP2R22 rs10741657 was the largest that was reported [25][26][27][28][29][30]. The difference in the genotype differences can be attributed due to the variance in the continent of origins, country of origins, and the population's race.…”
Section: Resultssupporting
confidence: 72%
“…In this research, the most common frequency distribution for the heterozygous genotype was the GA genotype, with 33 people (39.3%), and the least common genotype was the AA genotype with 20 people (23.8%). This result is in accordance with a study on healthy individuals in Denmark, and a study on unhealthy individuals in Jordan, Serbia, and Chennai (India), where the GA genotype of CYP2R1 rs10741657 was the largest genotype amount that was reported, but it was not in accordance with a study with healthy subjects in Singapore, Jordan, and Bangladesh, that reported the GG genotype in CYP2R22 rs10741657 was the largest that was reported [25][26][27][28][29][30]. The difference in the genotype differences can be attributed due to the variance in the continent of origins, country of origins, and the population's race.…”
Section: Resultssupporting
confidence: 72%
“…An SNP (rs1041657) in the CYP2R1 gene has been correlated with vitamin D differences in serum. For instance, studies have reported that individuals carrying the G allele had lower vitamin D levels in serum, concluding that the rs1041657 has a vital role in determining vitamin D levels ( 40 , 41 ). The frequency of the G allele in Latin America is 0.64, whereas for the A allele is 0.36 ( 20 ).…”
Section: Genetics In Obesity In the Latin American Populationmentioning
confidence: 99%
“…Various human genetics studies have associated PCSK1 with metabolic phenotypes such as early onset obesity, intestinal malabsorption, gastrointestinal complications, diabetes, and reactive hypoglycemia ( 38 , 39 ). The availability of various PCSK1 mouse models made it possible to investigate its function and expression in different tissues (brain, brainstem, pancreas, intestine, stomach, and immune cells) ( 40 , 41 ).…”
Section: Genomics and Diet Interaction In Obesity In The Latin Americ...mentioning
confidence: 99%
“…Связь полиморфизма РВD rs10741657 с уровнем витамина D в сыворотке крови была подтверждена в двух исследованиях (одно -среди европейцев, другое -азиатов) [8,9]. В исследовании, прове денном в в Республике Бангладеш, показано, что носители двух аллелей G (G/G) имеют более низкий уровень витамина D, чем носители одного аллеля (A/G), которые, в свою очередь, в среднем имеют более низкий уровень витамина D, чем индивидуу мы с генотипом A/A [10].…”
Section: Introductionunclassified